Applying Benford’s law to detect earnings management - Sylwestrzak Marek (Journal of Economics and Management, 2023)
– This paper analyzes the role of Benford’s law in the detection of earnings management in Poland. Previous research that uses Benford’s law does not split the sample into a fraud and a control group; however, this method is used in logistic regression and data mining analysis.